Sailing on the Atlântico Pardo, or the lusophony reinvented - Schmidt, Simone Pereira (2006)
The present paper discusses the Portuguese colonial project and its developments relating to gender and race. It begins by analyzing the motivation for the trip and for the transnational routes in Atlântico Negro by Paul Gilroy. In order to reflect on the "lusofonia" (Portuguese-speaking countries) and its implications, two novels are discussed: Nação Crioula and O ano em que Zumbi tomou o Rio, both by the Angolan writer José Eduardo Agualusa.